Influence of production situation on the incidence of brown spot of rice (Oryza sativa) caused by Bipolaris oryzae in the Philippines - Macasero, John Bethany M.; Castilla, Nancy P.; Pangga, Ireneo B.; Marquez, Leonardo V.; Martin, Edwin C.; Duque, Ulysses G.; Laborte, Alice G. (Wiley, 2024)
Brown spot, caused by Bipolaris oryzae, is becoming more prevalent and important in the Philippines but risk assessment is limited. Surveys of 2186 farmers' fields were conducted in the major rice‐growing areas in the country from 2015 to 2018 to analyse the components of production situation (PS) that contribute to the area under the progress curve of brown spot incidence (aBS). Based on lasso regression, the components of PS that influence aBS, in decreasing order, are ecosystem (irrigated vs. rainfed), crop establishment method (direct seeding vs. transplanting), variety type (hybrid vs. inbred), rate of phosphorus fertilizer, rate of potassium fertilizer, application of organic fertilizer (with vs. without organic fertilizer) and frequency of fungicide application. Pairwise comparisons showed that aBS is positively associated with direct‐seeded rice, rainfed ecosystem, hybrid rice, moderate to high P and K rates and spraying of fungicide. Correspondence analysis and chi‐squared tests showed that the class with highest aBS is closely associated with the production situation characterized by rainfed ecosystem, direct‐seeded rice, fungicide application, moderate nitrogen and moderate to high phosphorus and potassium rates; and weather pattern (temperature, relative humidity, solar radiation, rainfall and wind speed) that occurs during the wet season. These results confirm previous studies showing that increased adoption of water‐saving technologies and direct seeding for adaptation and mitigation to climate change and reduction of agricultural labour, will most probably favour brown spot. Strategies to manage the disease under these production situations should be implemented in government programmes and considered in future research agendas.